2005
DOI: 10.1002/ange.200500577
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Enhanced Protein Stability through β‐Turn Optimization: Insights for the Design of Stable Peptide β‐Hairpin Systems

Abstract: Ein guter Dienst: Haarnadelschleifen sind eine wichtige Komponente von Proteinstrukturen und Ausgangspunkte für die β‐Haarnadel‐Faltung. Mit Ubiquitin als „Wirt“‐System (siehe Struktur) wurden Protein‐Engineering‐Methoden verwendet, um den Energiebeitrag von Typ‐I′‐Haarnadelschleifen zur Stabilität von Proteinen zu bestimmen, wobei das Ziel war, das rationale Design von Modell‐Peptidsystemen zu optimieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 68 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…Accordingly, hairpins in folding nuclei show high Φ values in both the two strands and the turn between them. 18,[51][52][53] Our success in stabilizing the N2 domain of G3P supports previous studies 6,8,29,37,54,55 that suggested consensus sequence optimization of turns, possibly in combination with in vitro selection, as an excellent and simple means for increasing the stability of a protein.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Accordingly, hairpins in folding nuclei show high Φ values in both the two strands and the turn between them. 18,[51][52][53] Our success in stabilizing the N2 domain of G3P supports previous studies 6,8,29,37,54,55 that suggested consensus sequence optimization of turns, possibly in combination with in vitro selection, as an excellent and simple means for increasing the stability of a protein.…”
Section: Discussionsupporting
confidence: 85%
“…These results are consistent with earlier substitutions in turns of α-spectrin SH3, 36 fibroblast growth factor-1, 37 lysozyme, 38 and ubiquitin. 6 …”
Section: Combination Of the Most Stable Designed Turn Sequencesmentioning
confidence: 97%
See 2 more Smart Citations
“…As one of the solutions to address the above mentioned problem, protein engineering has been successfully utilized to improve the thermostabilities of enzymes elsewhere (Gåseidnes et al, 2003;Korkegian et al, 2005;Simpson et al, 2005;Wunderlich et al, 2005;You et al, 2010). Unlike other stabilization methods (e.g.…”
Section: Q3mentioning
confidence: 99%